2019
DOI: 10.14740/wjon1228
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neurofilament Light, Glial Fibrillary Acidic Protein and Tau Are Possible Serum Biomarkers for Activity of Brain Metastases and Gliomas

Abstract: BackgroundPrimary central nervous system (CNS) tumors and brain metastases (BMs) are major causes of morbidity and mortality, accompanied by low survival rates. Efforts to early discovery of CNS malignancies are critical. However, to date, there are no biomarkers approved for detection of cancer activity in the brain. Blood levels of neurofilament light (NfL) and tau, as well as glial fibrillary acidic protein (GFAp), show promise as biomarkers for brain injury in previous studies. Therefore, we performed a cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 34 publications
1
41
0
Order By: Relevance
“…Hence, a release of NfL would be expected as a consequence of the neuronal damage caused by the infiltration of the brain metastasis in the brain parenchyma [ 18 ] and/or brain compression caused by the metastasis. In line with this, a recent study found elevated NfL levels in seven cancer patients with brain metastasis compared with healthy controls [ 19 ], which supports our findings.…”
Section: Discussionsupporting
confidence: 93%
“…Hence, a release of NfL would be expected as a consequence of the neuronal damage caused by the infiltration of the brain metastasis in the brain parenchyma [ 18 ] and/or brain compression caused by the metastasis. In line with this, a recent study found elevated NfL levels in seven cancer patients with brain metastasis compared with healthy controls [ 19 ], which supports our findings.…”
Section: Discussionsupporting
confidence: 93%
“…If an experimental therapeutic agent affected these other processes, it may change biomarker levels independently of any effect on neurodegeneration. Plasma tau and NfL have some appealing and complementary properties as therapeutic markers, and notably different half-lives in blood 30 , but their suitability should be evaluated directly in patients receiving putative treatments. It would also be useful to study them in animal models in which successful treatment of prion disease can be achieved 11 .…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of GFAP following reactive astrogliosis and destruction of astrocyte structural integrity combined with blood–brain barrier disruption may lead to increased sGFAP levels in patients with BMs [ 26 , 27 ]. Although an increasing number of studies reported the roles of sNFL and sGFAP in various neurological disorders, data are scarce for patients with BMs [ 28 , 29 ]. Hepner et al showed higher concentrations of sNfL and sGFAP in 22 patients with gliomas or BMs compared to those in nine patients without BMs [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although an increasing number of studies reported the roles of sNFL and sGFAP in various neurological disorders, data are scarce for patients with BMs [ 28 , 29 ]. Hepner et al showed higher concentrations of sNfL and sGFAP in 22 patients with gliomas or BMs compared to those in nine patients without BMs [ 28 ]. Another recent study showed higher sNfL levels in 43 patients with BMs compared to those observed in 25 without BMs, although there was no age-matching in the comparison [ 29 ].…”
Section: Discussionmentioning
confidence: 99%